Harnessing the multi-targeted potential of rehmanniae radix natural products against renal fibrosis: a mechanistic review - Zhao, Keqin; Zhu, Han; Zheng, Liping; Wang, Wenru; Liu, Peng; Yu, Renhuan; Ma, Xiaobei (Frontiers in Pharmacology, 2025)
Renal fibrosis represents the final common pathological pathway of nearly all chronic kidney disease (CKD), yet effective therapeutic options remain profoundly limited. Rehmanniae Radix, a botanical drug in Traditional Chinese Medicine (TCM), has a long history of use for its nephroprotective properties. However, a systematic, mechanism-based understanding of how its natural products combat renal fibrosis is conspicuously absent. Herein, we present a comprehensive review to dissect the multi-component, multi-target, and multi-pathway mechanisms through which the major active ingredients of Rehmanniae Radix ameliorate renal fibrosis. Our analysis reveals that these natural products, including Acteoside (also known as Verbascoside), Catalpol, and Rehmannioside A, converge upon the inhibition of the canonical TGF-β1/Smad signaling pathway—a master regulator of fibrosis. This analysis focuses primarily on evidence from preclinical (in vivo and in vitro) models, as rigorous clinical data on the efficacy of these specific constituents remain limited. Furthermore, they exert potent anti-inflammatory and antioxidant effects via the modulation of pivotal signaling nodes such as NF-κB, Nrf2, and TLR4. Critically, this review illuminates unique and novel mechanisms, including the enhancement of autophagy by Acteoside and the targeted inhibition of the AT1R/MAPK14/IL-17 axis by Rehmannioside A in hypertensive nephropathy. By elucidating this intricate pharmacological network, this review not only decodes the scientific basis for the nephroprotective effects of Rehmanniae Radix but also provides a theoretical foundation for the development of novel anti-fibrotic therapies and identifies promising molecular targets for future investigation.